The Influence of History Learning on the Nationalist Attitudes of Class XI IPS Students at SMA Muhammadiyah 1 Karanganyar - Saputri, Nurul Riri; Saraswati, Ufi (Universitas Negeri Semarang, 2016)
This research aims to: (1) Understand the history learning process. (2) Knowing students' nationalistic attitudes. (3) Knowing the influence of history learning on the nationalistic attitudes of class XI IPS students at SMA Muhammadiyah 1 Karanganyar. This research method is quantitative regression with an ex post facto design. The data source for this research is class XI IPS students at SMA Muhammadiyah 1 Karanganyar. The data for this research are from class XI IPS students. The research target is the history learning process and students' nationalist attitudes. Data collection techniques use questionnaires and documentation. The data analysis technique uses descriptive percentage analysis with Ms. Excel 2010 and statistical analysis using the SPSS 16 application. The results of this research are: (1) Based on descriptive analysis using Ms. Excel 2010, class XI IPS history learning is in a good category with an average of 71.78. (2) Based on descriptive analysis using Ms. Excel 2010, the nationalism attitude of the class was high with an average of 89.2. So the nationalism attitude of class XI IPS students is in the very high category with an average of 87.22. (3) There is an influence of history learning on students' nationalistic attitudes of 0.150 (15%) and the remaining 85% is influenced by other factors.